2024 Surprise Inlet Landslides: Insights From a Prototype Landslide‐Triggered Tsunami Monitoring System in Prince William Sound, Alaska - Ezgi Karasözen; Michael E. West; Katherine R. Barnhart; John J. Lyons; Terry Nichols; Lauren N. Schaefer; Bohyun Bahng; Summer Ohlendorf; Dennis M. Staley; Gabriel J. Wolken (Geophysical Research Letters, 2025)
Abstract Alaska's coastal communities face growing landslide hazards owing to glacier retreat and extreme weather intensified by the warming climate, yet hazard monitoring remains challenging. As part of ongoing experimental monitoring in Prince William Sound, we detected three large landslides (0.5–2.3 M m3) at Surprise Inlet on 20 September 2024, within the span of an hour. These events were identified in near real‐time through seismic data and later confirmed using satellite imagery, tidal records, and infrasound. The landslides generated a modest tsunami, and a 4 cm wave was recorded by a tide gauge 18 km away, marking the first recorded landslide to reach water since monitoring began in this region in 2021. Here, we examine the detection and interpretation of these landslides using multiple data sources and modeling. We demonstrate the effectiveness of this regional seismic monitoring system and show how complementary instrumentation, where available, can enhance detection capabilities.